2022
DOI: 10.7717/peerj.14447
|View full text |Cite
|
Sign up to set email alerts
|

Ear your heart: transcutaneous auricular vagus nerve stimulation on heart rate variability in healthy young participants

Abstract: Background Transcutaneous auricular vagus nerve stimulation (taVNS) stimulating the auricular branch of the vagus nerve along a well-defined neuroanatomical pathway, has promising therapeutic efficacy. Potentially, taVNS can modulate autonomic responses. Specifically, taVNS can induce more consistent parasympathetic activation and may lead to increased heart rate variability (HRV). However, the effects of taVNS on HRV remain inconclusive. Here, we investigated changes in HRV due to brief alteration periods of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…For the latter, similar observations were made for chronic invasive stimulation of the left cervical vagus nerve as an add-on treatment for medically refractory epilepsy ( Constantinescu et al, 2019 ; Wu et al, 2021 ). Studies on cardiac effects of short-term (minutes to hours) taVNS have so far been performed in healthy subjects only, however, with conflicting findings ( De Couck et al, 2017 ; Badran et al, 2018 ; Capilupi et al, 2020 ; Keute et al, 2021 ; Machetanz et al, 2021a ; Machetanz et al, 2021b ; Wolf et al, 2021 ; Forte et al, 2022 ). These can probably be related to stimulation-parameter-dependent influences that act on brain-heart couplings ( Cerritelli et al, 2021 ; Keute et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…For the latter, similar observations were made for chronic invasive stimulation of the left cervical vagus nerve as an add-on treatment for medically refractory epilepsy ( Constantinescu et al, 2019 ; Wu et al, 2021 ). Studies on cardiac effects of short-term (minutes to hours) taVNS have so far been performed in healthy subjects only, however, with conflicting findings ( De Couck et al, 2017 ; Badran et al, 2018 ; Capilupi et al, 2020 ; Keute et al, 2021 ; Machetanz et al, 2021a ; Machetanz et al, 2021b ; Wolf et al, 2021 ; Forte et al, 2022 ). These can probably be related to stimulation-parameter-dependent influences that act on brain-heart couplings ( Cerritelli et al, 2021 ; Keute et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies, which have investigated effects of vagus nerve stimulation on HRV, have generated various results depending on the study design, such as included population, the region of stimulation and its duration, and methods of HRV analysis. Some studies using TAVNS for shorter periods (5 or 10 min) in healthy subjects have also showed significant improvement in HRV parameters of parasympathetic activity (Forte et al 2022;Geng et al 2022). However, regarding the LH component, it is suggested that prolonged TAVNS stimulation (30 -60 min) is required to decrease its power (Tran et al 2019).…”
Section: A Single Session Of Tavns Reduces Hr and Improves Sympathova...mentioning
confidence: 98%
“…Recognized as a potentially safe and feasible treatment, it is imperative for upcoming research on taVNS to meticulously evaluate any adverse events (73). Moreover, there is evidence indicating that taVNS can amplify cardiac vagal activity, reflected by heart rate variability (HRV) (74). Consequently, we speculate that, unlike the invasive implanted VNS, taVNS might serve as a pivotal tool in future studies on preeclamptic women to potentially alleviate their symptoms and possibly mitigate neurodevelopmental damage in their offspring.…”
Section: Modulation Of Vagal Nerve Activity and Potential Application...mentioning
confidence: 99%